Concurrent infection with porcine reproductive and respiratory syndrome virus and Haemophilus parasuis in two types of porcine macrophages: apoptosis, production of ROS and formation of multinucleated giant cells - Kavanová, Lenka; Matiašková, Katarína; Levá, Lenka; Štěpánová, Hana; Nedbalcová, Kateřina; Matiašovic, Ján; Faldyna, Martin; Salát, Jiří (Veterinary research, 2017)
Porcine reproductive and respiratory syndrome (PRRS) is one of the most significant and economically important infectious diseases affecting swine worldwide and can predispose pigs to secondary bacterial infections caused by, e.g. Haemophilus parasuis. The aim of the presented study was to compare susceptibility of two different types of macrophages which could be in contact with both pathogens during infection with PRRS virus (PRRSV) and in co-infection with H. parasuis. Alveolar macrophages (PAMs) as resident cells provide one of the first lines of defence against microbes invading lung tissue. On the other hand, monocyte derived macrophages (MDMs) represent inflammatory cells accumulating at the site of inflammation. While PAMs were relatively resistant to cytopathogenic effect caused by PRRSV, MDMs were much more sensitive to PRRSV infection. MDMs infected with PRRSV increased expression of pro-apoptotic Bad, Bax and p53 mRNA. Increased mortality of MDMs may be also related to a higher intensity of ROS production after infection with PRRSV. In addition, MDMs (but not PAMs) infected with H. parasuis alone formed multinucleated giant cells (MGC); these cells were not observed in MDMs infected with both pathogens. Higher sensitivity of MDMs to PRRSV infection, which is associated with limited MDMs survival and restriction of MGC formation, could contribute to the development of multifactorial respiratory disease of swine.
Keywords: hemofilové infekce; reaktivní formy kyslíku; Haemophilus Infections; Porcine respiratory and reproductive syndrome virus; Pyrimidines; sulfonamidy; pyrimidiny; Macrophages; reprodukční a respirační syndrom prasat; Reactive Oxygen Species; Swine; Sulfonamides; zvířata; Haemophilus parasuis; koinfekce; Giant Cells; makrofágy; prasata; Porcine Reproductive and Respiratory Syndrome; Coinfection; obrovské buňky; virus reprodukčního a respiračního syndromu prasat; Animals